PENGARUH TAKARAN MEDIA BALITHI TERHADAP PERTUMBUHAN DAN PRODUKSI DAUN LEATHERLEAF FERN (Rumohra adiantiformis) (G.Forst.) Ching) - Ika Rahmawati; E. Dwi S Nugroho (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
Leatherleaf fern (Rumohra adiantiformis) could be the cut leaves of ornamental plants as a filler andbouquet. Growing media is one of the important factors to produced growth and yields of leatherleaf.The research aims to study the effects of several dosage Balithi’s media could support to maximizinggrowth and yields of leatherleaf. The research was conducted at IOCRI (Indonesia Ornamental CropResearch Institute) in June 2014 - December 2015. Experiment used a randomized block design(RBD) two factors with four replications. The size of each plot treatment was 1.2 × 2.1 m. The firstfactor was the Balithi’s media, namely: 1 dosage Balithi’s media without gliocompos (M1), 1 dosageBalithi’s media with gliocompos (M2), and ½ dosage Balithi’s media with ½ dosage gliocompos(M3). The second factor was the leatherleaf varieties, namely Florida (V1) and Mayfield (V2). Theresult showed that treatment variety was significantly affected the parameters of crown height, lengthof strands and number of leaves per plot. The varieties Mayfield growth better than Florida. TheMayfield variety produced 3,961 strands and Florida variety 2,160 strands. M3 was the best media;M3 produced 1,268 leaves, M2 1,082 leaves and M1 1,067 leaves. The best media for growth andyields was M3 (½ dosage Balithi’s media + ½ dosage gliocompos).